In situ mapping of normal strains in the field of a growing fatigue crack in a steel weld using digital image correlation and energy dispersive synchrotron X-ray diffraction - Wigger, T; Lupton, C; Alshammrei, S; Tong, J; Marrow, TJ; Earp, P; Zhu, M; Wang, Q; Connolley, T (Elsevier, 2018)
Fatigue crack growth in the Heat Affected Zone (HAZ) of a welded CrNiMoV steel has been investigated, in situ, using Digital Image Correlation (DIC) and Energy Dispersive X-Ray Diffraction (EDXD). Compact tension specimens of welded joint were loaded under tension-tension cyclic loading. The crack tip position and the evolution of the near-tip strains normal to the crack plane were tracked at selected positions for a growing fatigue crack both on the specimen surface using DIC and in the bulk of the specimen using EDXD of synchrotron X-rays. The uncertainty and quality of the DIC measurements were examined with regard to some of the key data processing parameters, including subset size and the size of measurement window; whilst the measurement errors in the EDXD measurements were also estimated. A “characteristic” strain was estimated, in the bulk of the specimen and on the specimen surface, from the average strains captured at selected positions when the propagating fatigue crack tip reached these positions.